Synthesis and investigation of antimicrobial activity of compounds derived from benzo[C][1, 2, 5]oxadiazole-1-oxides and phenolates. Issue 18 (16th September 2016) - Chugunova, Elena A.; Akylbekov, Nurgali I.; Voloshina, Alexandra D.; Kulik, Natalia V.; Zobov, Vladimir V.; Babaev, Vasily M.; Gavrilov, Nikolai V.; Burilov, Alexander R.
ABSTRACT: (Di)chloro(di)nitrobenzofuroxans form substitution products involving carbon atoms with phenolates in isopropyl alcohol medium. In the case of 4, 6-dinitro-5, 7-dichlorobenzofuroxan, besides replacement of one chlorine atom and the formation of C -bonded product, we observed the hydrolysis of the second chlorine and replacement of it by hydroxyl group. Products of reaction of 4, 6-dichloro-5-nitrobenzofuroxan with phenolates display excellent antimicrobial activity and have dual action, both against bacteria and fungi. GRAPHICAL ABSTRACT: